O Currículo Oficial de Geografia do Estado de São Paulo e os Conceitos Geográficos Escolares - Santos, Lílian Maria dos [UNESP] (2013)
This work is linked to the search line Public Policy, School Organisation and Teacher Training, in the Post-Graduation in Education, in the Faculty of Science and Technology of the Universidade Estadual Paulista (UNESP), Presidente Prudente campus - SP. This work is an analysis of the current Official Curriculum of Geography for Elementary School Cycle II in São Paulo, with the purpose of reflecting on the importance of school Geographical Concepts, inserted in the Official Curriculum document of the State of São Paulo (COESP). The research was directed towards an investigation of the Geography Curriculum contextualizing Geographical Concepts and changes in the state education. Thus, analysis of curriculum theories was performed in a debate that included the various conceptions of curriculum, Geography and its teaching, focus on understanding the methodological theoretical perspective inserted in the material, beyond the understanding of its genesis and implications contained in the educational policy process in relation to this new Curriculum. Thus, along with the literature, allowing us greater understanding of the subject, we sought the articulation between the methodology of documentary analysis, qualitative techniques and interviews...